Common Coupled Fixed Point Theorems on C⋆-Algebra-Valued Partial Metric Spaces - Gunaseelan Mani; Arul Joseph Gnanaprakasam; Precious B. Khumalo; Yaé U. Gaba (Journal of Function Spaces)
In this paper, we prove common coupled fixed point theorems on complete C⋆-algebra-valued partial metric spaces. An example and application to support our result are presented.